2006
DOI: 10.1091/mbc.e06-06-0496
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Attachment and Generation of Mature Focal Adhesions by Integrin-containing Filopodia in Cell Spreading

Abstract: Integrin receptors, and associated cytoplasmic proteins mediate adhesion, cell signaling and connections to the cytoskeleton. Using fluorescent protein chimeras, we analyzed initial integrin adhesion in spreading fibroblasts with Total Internal Reflection Fluorescence (TIRF) microscopy. Surprisingly, sequential radial projection of integrin and actin containing filopodia formed the initial cell-matrix contacts. These Cdc42-dependent, integrin-containing projections recruited cytoplasmic focal adhesion (FA) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
141
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 38 publications
15
141
0
Order By: Relevance
“…Interestingly, depending on the analyzed cell type filopodial, sensing does not necessarily have to end up in cell matrix adhesions as described, for example, 3T3 fibroblasts during cell spreading. 8 Instead, filopodia can also mediate the interaction between macrophages and pathogens 36 or between two cells as shown for embryonic epithelial cells 37 or the formation of functional neuronal interactions. 38 These examples show the overall importance of filopodial sensing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, depending on the analyzed cell type filopodial, sensing does not necessarily have to end up in cell matrix adhesions as described, for example, 3T3 fibroblasts during cell spreading. 8 Instead, filopodia can also mediate the interaction between macrophages and pathogens 36 or between two cells as shown for embryonic epithelial cells 37 or the formation of functional neuronal interactions. 38 These examples show the overall importance of filopodial sensing.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Furthermore, for many cell types the lamellipodium is described as the origin of adhesion site formation. 7 In addition, for cell types forming filopodia latest research has shown an important role of these finger-like extensions in cell spreading 8 and adhesion assembly during migration. 9,10 Here, nearly all lamellipodial focal adhesions (FAs) evolve from small focal complexes (FXs) originally assembled within filopodia and just increased in size when overgrown by the lamellipodial leading edge.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be argued that the variation of the contact area and its increasing rate can be used to quantify cell viability. In a previous study (Partridge and Marcantonio 2006), the two-dimensional area that was spread by cells that are transfected by different plasmids was measured by using phase-contrast microscopy and TIRF microscopy. The findings of Partrige and Marcantonio (2006) that the increasing rate of the spread area varied with the transfecting material and that the area range was 100Â400 mm 2 are quite comparable to the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Nutrition is supplied during the experiment from the incubator through the chip system. In the literature (Lanni et al 1985;Bretschneider et al 2004;Weisswange et al 2005;Partridge and Marcantonio 2006;Manneville 2006), there are many examples of the use of EF in combination with TIRF for measuring global and membrane-specific events. However, in the present study, EF setup was used only for illuminating the whole field to locate the cells before and/or after the TIRF images were recorded.…”
Section: Quantification Of Cellular Contact and Lift-off 387mentioning
confidence: 99%
See 1 more Smart Citation